Proposing a Model of Impression Learning Program to Foster Elementary Students’ Mathematics Skills in an Islamic Context - Sri Mellia Marinda; Nur Hayati; Rahmat Kurnia (KEDJATI Foundation, 2024)
This research was intended to portray how Impression Learning (IL) programs were incorporated into a mathematics class in an Indonesian Islamic elementary school and how the students’ mathematics skills were fostered during the learning process. This study was a classroom practice-based model of how the IL programs were conveyed in the detailed teaching of equality of money value in grade 2 of elementary school. This study used a case study to see how a phenomenon happened: teaching steps, teacher-student dialogues, and involvement of students in the learning process. Also, the use of concrete material was planned to enable students' senses and became a novelty of this study. In addition, the teaching process consisted of (a) a learning plan (setting the learning objectives, learning materials and resources, learning media, learning approaches and strategies, schedules, and learning environments), (b) combining the concepts of teaching procedures: Talqiyyan Fikriyyan, TANDUR (Grow, Experience, Name, Demonstrate, Repeat, and Celebration), installing an internalization of Islamic values, and reflection. Besides, this research could optimize students thinking and attitude patterns. Hence, this study provides an alternative model of impression teaching in education, especially mathematics.